Metabolic theory of ecology successfully predicts distinct scaling of ectoparasite load on hosts. Issue 1917 (18th December 2019) - Hechinger, Ryan F.; Sheehan, Kate L.; Turner, Andrew V.
Abstract : The impacts of parasites on hosts and the role that parasites play in ecosystems must be underlain by the load of parasites in individual hosts. To help explain and predict parasite load across a broad range of species, quantitative theory has been developed based on fundamental relationships between organism size, temperature and metabolic rate. Here, we elaborate on an aspect of that 'scaling theory for parasitism', and test a previously unexplored prediction, using new data for total ectoparasite load from 263 wild birds of 42 species. We reveal that, despite the expected substantial variation in parasite load among individual hosts, (i) the theory successfully predicts the distinct increase of ectoparasite load with host body size, indicating the importance of geometric scaling constraints on access to host resources, (ii) ectoparasite load appears ultimately limited by access—not to host space—but to host energy, and (iii) there is a currency-dependent shift in taxonomic dominance of parasite load on larger birds. Hence, these results reveal a seemingly new macroecological pattern, underscore the utility of energy flux as a currency for parasitism and highlight the promise of using scaling theory to provide baseline expectations for parasite load for a diversity of host species.